2009
DOI: 10.1002/chin.200937117
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Microwave Assisted Rapid and Efficient Synthesis of New 3‐Ethoxy‐4,6‐diaryl‐4,5‐dihydro‐2,1‐benzisoxazoles.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The latter compound arises from the Robinson annelation between the chalcone and acetoacetamide without incorporation of ammonia, and was unambiguously identified by its independent synthesis from chalcone and acetoacetamide in the presence of piperidine. 30 While subsequent experiments showed that the use of a higher catalyst load (entry 2, Table 1) or a more concentrated solution (entry 3, Table 1) did not greatly improve the results, a longer reaction time (15 h) was found to be highly beneficial, leading almost exclusively to the target compound 3a (entry 4, Table 1). A control experiment carried out under the same conditions but in the absence of catalyst also led to consumption of the starting materials and to the formation of 3a, but in this case a higher amount of the side product 5 was observed (entry 5, Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The latter compound arises from the Robinson annelation between the chalcone and acetoacetamide without incorporation of ammonia, and was unambiguously identified by its independent synthesis from chalcone and acetoacetamide in the presence of piperidine. 30 While subsequent experiments showed that the use of a higher catalyst load (entry 2, Table 1) or a more concentrated solution (entry 3, Table 1) did not greatly improve the results, a longer reaction time (15 h) was found to be highly beneficial, leading almost exclusively to the target compound 3a (entry 4, Table 1). A control experiment carried out under the same conditions but in the absence of catalyst also led to consumption of the starting materials and to the formation of 3a, but in this case a higher amount of the side product 5 was observed (entry 5, Table 1).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The first experiment (entry 1, Table ) was performed in refluxing ethanol and in the presence of ceric ammonium nitrate because of our experience in the use of this reagent as a catalyst in a somewhat related tetrahydropyridine synthesis from β-dicarbonyl compounds, acrolein, and primary amines in the presence of ethanol and provided a rather complex mixture of the desired compound 3a , the corresponding dihydropyridine 4 and a small amount of compound 5 . The latter compound arises from the Robinson annelation between the chalcone and acetoacetamide without incorporation of ammonia, and was unambiguously identified by its independent synthesis from chalcone and acetoacetamide in the presence of piperidine . While subsequent experiments showed that the use of a higher catalyst load (entry 2, Table ) or a more concentrated solution (entry 3, Table ) did not greatly improve the results, a longer reaction time (15 h) was found to be highly beneficial, leading almost exclusively to the target compound 3a (entry 4, Table ).…”
Section: Resultsmentioning
confidence: 99%